Alpha-Glucosidase Inhibitors Alter Gut Microbiota and Ameliorate Collagen-Induced Arthritis - Zhang, Lingshu; Song, Pingfang; Zhang, Xiaowei; Metea, Christina; Schleisman, Matthew; Karstens, Lisa; Leung, Eric; Zhang, Jun; Xu, Qiang; Liu, Yi; Asquith, Mark; Chu, Cong-Qiu (Frontiers in Pharmacology, 2020)
Acarose is an anti-diabetic drug and exhibited anti-arthritic effects. We hypothesized that acarbose influences the gut microbiota that affects the course of arthritis and tested this hypothesis in collagen-induced arthritis (CIA). Acarbose in drinking water was administered via gastric gavage started prior to or at the time of CIA induction. Fecal pellets were collected before arthritis induction, during onset of arthritis and after treatment for identification of bacteria using16S rDNA sequencing. Changes of T helper-17 (Th17) and T regulatory (Treg) cells of intestine and spleen, and serum cytokines were analyzed. Administration before induction of CIA, acarbose significantly reduced the incidence of arthritis and attenuated clinical severity of arthritis. The frequency of Th17 cells was significantly decreased in the intestinal lamina propria in acarbose treated mice. Mice were treated with acarbose prophylactically showed significantly increased CD4+CD25+Foxp3+ Treg cells with elevation of Helios and CCR6. A remarkable alteration in microbial community was observed in acarbose treated mice. Bacterial diversity and richness in mice with arthritis were significantly lower than those in acarbose treated groups. The frequency of Firmicutes was significantly reduced after arthritis onset but was restored after treatment with acarbose. The frequency of Lactobacillus, Anaeroplasma, Adlercreutzia, RF39 and Corynebacterium was significantly higher in control groups than in acarbose treated, while Oscillospira, Desulfovibrio and Ruminococcus enriched in acarbose treated group. Miglitol, another α-glucosidase inhibitor showed similar anti-arthritic effect to that of acarbose but less potent. These data demonstrated that acarbose alleviated CIA through regulation of Th17/Treg cells in the intestinal mucosal immunity which might be resulted from impact of the drug on gut microbial community. The inexpensive antidiabetic drugs with an excellent safety profile is potentially useful for management of rheumatoid arthritis.